DIMENSIKEMISKINANDANUPAYAMENGATASIMASALAHNYA - Sriadi Setyawati (Universitas Negeri Yogyakarta, 2012)
Kemiskinanmerupakanpermasalahanyangkompleks,makadalampengentasankemiskinantidakdapathanyadifokuskanpadapeningkatanekonomisajatetapiharusterpadu.Sehinggapersoalanpotensikualitassumberdayamanusiadanpenduduk,sertawilayah,kebutuhan,kendalaatauhambatandanindikatorsecaraoperasionalmenjadipentinguntukdiketahui.Olehkarenaitusebelummenentukansuatukebijakanatauprogram–program,terlebihdahuludilakukaninventarisasidanidentifikasipotensikualitassumberdayamanusiadanpenduduksertawilayah,kebutuhan,kendalaatauhambatanyangada.Karenadenganinventarisasidanidentifikasipotensikualitassumberdaya,dapatdiketahuivariasikarakteristikwilayahyangberbedapadatingkatnasional,propinsi,kabupaten,kecamatandankelurahan.Partisipasimasyarakatmerupakan“ujungtombak”untukmencapaitujuandansasaransepertiyangdiharapkan,makamengikutsertakanmasyarakatdalamimplementasiprogrampengentasankemiskinanmerupakansuatukeharusan.Belumoptimalnyaprogrampengentasankemiskinandisebabkanlemahnyainventarisasidanidentifikasipotensikualitassumberdayamanusia,pendudukdanwilayah.Sertalemahnyainventarisasidanidentifikasikebutuhandankendalaatauhambatanyangada.Katakunci:sumberdaya,inventarisasi,identifikasi.